Clinical trials in pediatric ALS: a TRICALS feasibility study. Issue 7 (2nd October 2022) - Kliest, Tessa; Van Eijk, Ruben P.A.; Al-Chalabi, Ammar; Albanese, Alberto; Andersen, Peter M.; Amador, Maria Del Mar; BrÅthen, Geir; Brunaud-Danel, Veronique; Brylev, Lev; Camu, William; De Carvalho, Mamede; Cereda, Cristina; et al.
Abstract: Background: Pediatric investigation plans (PIPs) describe how adult drugs can be studied in children. In 2015, PIPs for Amyotrophic Lateral Sclerosis (ALS) became mandatory for European marketing-authorization of adult treatments, unless a waiver is granted by the European Medicines Agency (EMA). Objective: To assess the feasibility of clinical studies on the effect of therapy in children (<18 years) with ALS in Europe. Methods: The EMA database was searched for submitted PIPs in ALS. A questionnaire was sent to 58 European ALS centers to collect the prevalence of pediatric ALS during the past ten years, the recruitment potential for future pediatric trials, and opinions of ALS experts concerning a waiver for ALS. Results: Four PIPs were identified; two were waived and two are planned for the future. In total, 49 (84.5%) centers responded to the questionnaire. The diagnosis of 44, 858 patients with ALS was reported by 46 sites; 39 of the patients had an onset < 18 years (prevalence of 0.008 cases per 100, 000 or 0.087% of all diagnosed patients). The estimated recruitment potential (47 sites) was 26 pediatric patients within five years. A majority of ALS experts (75.5%) recommend a waiver should apply for ALS due to the low prevalence of pediatric ALS. Conclusions: ALS with an onset before 18 years is extremely rare and may be a distinct entity from adult ALS. Conducting studies on the effect of disease-modifying therapy in pediatric ALS may involve lengthy recruitment periods, high costs, ethical/legal implications, challenges in trial design and limited information.